IMPROVING THE STUDENTS’CHIEVEMENT IN WRITING DESCRIPTIVE TEXT BY USING REALIA STRATEGY - Finny Ameliana Br Surbakti and Amrin Saragih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study attempted to improve students’ writing descriptive textby using Realia Strateg. This study was conducted by using classroom action research. The subject of the research was class VIII SMP NEGERI 1 SALAPIAN which consisted of 30 students. The research was conducted in two cycles and every cycle consisted of three meetings. The instruments for collecting the data were quantitative data (Writing Test) and qualitative data (diary notes, observation sheet and questionnaire sheet). Based on Writing scores, students’ score kept improving in every evaluation. In the test I the mean was 70,36, in the test II the mean was 86.13 . Based on observation sheet and questionnaire, it was found that teaching-learning process ran well. Students were active, enthusiastic, and interested in writing descriptive text. The result of the research showed that applying possible sentence strategy significantly improved students’ writing achievement.